A Spectrum of Unusual Neuroimaging Findings in Patients with Suspected Sturge-Weber Syndrome - Adams, M.E.; Aylett, S.E.; Squier, W.; Chong, W. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Sturge-Weber syndrome (SWS) is frequently associated with neurologic complications such as seizures, so diagnosing this condition has important implications for patient management. The purpose of this study was to report unusual neuroimaging findings in patients with facial port-wine stain (PWS) and clinically suspected SWS.MATERIALS AND METHODS: Cranial MR imaging was reviewed for all children with facial port-wine stain (PWS) involving the upper face and eyelids who were referred to Great Ormond Street Hospital between 2003 and 2007 for investigation of suspected SWS. Patients were excluded from further analysis if the imaging findings were normal on initial and subsequent scans and the subject remained free of neurologic disease, or if the imaging showed the well-recognized pattern of exclusively supratentorial pial enhancement representing the pial angioma of SWS. For the remaining patients, the neurologic, dermatologic, and ophthalmologic records were examined and all available imaging was reviewed by a neuroradiologist. We documented the presence and distribution of pial enhancement; corroborative features of SWS, such as atrophy, calcification, choroid plexus changes, and ocular abnormalities; and all other intracranial abnormalities.RESULTS: Of the 62 patients referred for assessment, imaging findings were considered typical of SWS in 32 (52%) and were normal or showed abnormalities attributable to an unrelated pathology in 20 (32%). Of the remaining 10 patients, in 7 (11%), there was evidence of a pial angioma in an unusual distribution involving infratentorial structures, with the angioma in 1 patient being diagnosed at postmortem only; in 2 (3%), there were imaging abnormalities with some features in common with typical SWS, such as subcortical calcification, but with no evidence of pial enhancement; in 1 (1.6%), the initial MR imaging finding was normal, but repeat imaging subsequently revealed pial enhancement.CONCLUSIONS: Involvement of infratentorial structures is common but may be relatively subtle and should be actively sought. Cases in which there are certain patterns of imaging abnormalities but an apparent absence of supratentorial pial enhancement on MR imaging may represent formes frustes of SWS; visualization of pial angiomatosis may also be delayed until later in childhood than expected.